Guardianship patient characteristics and outcomes in geriatric social work practice: Australian context. (21st October 2021) - Jackman, Matthew; McDermott, Fiona; Sadler, Jacinta; El Hage, Nicole; Lee, Halim
ABSTRACT: This study explored the patient characteristics and outcomes in relation to guardianship in a large-scale sub-acute Australian hospital. Fifteen patients who appointed a guardian at The Kingston Center, Monash Health, participated through exploratory data collection and analysis utilizing a de-identifiable template. The findings revealed both diverse and complex patient characteristics, and ethical dilemmas in patient outcomes for social workers. Patient outcomes post-guardianship appointment and discharge highlighted a negative impact from long length of stay and the iatrogenic impact on patient wellbeing in hospital. The study reflected a disparity between patients' discharge goals and their outcomes indicating significant ethical dilemmas and complexities for social workers in ensuring rights to autonomy and responsibility for safety are balanced.